RETREATABILITY OF BIOCERAMIC SEALERS UESD WITH SINGLE CONE OBTURATION: SEM ASSESSMENT - KHALID, NISHTIMAN SHINO; AL-MEZORY, ADULLKAREEM RAMAZAN (Journal of Duhok University, 2023)
Aim: The aim of this study is to evaluate the retreatability of bioceramic sealers (Endosequence BC, Totalfill BC, MTA-Fillapex) used with single cone obturation technique. Materials and methods: Root canal of forty single rooted human mandibular premolar teeth were prepared with ProTaper Next rotary system up to X3 and obturated with single cone technique (n=10) using endosequence BC (A), Totallfill BC (B), MTA-Fillapex (C) and Zinc oxide (D) sealer, after two weeks, all samples retreated with ProTaper Universal Retreatment rotary files. regaining of working length and apical patency was evaluated. All samples longitudinally sectioned and assessed by Scanning electron microscope to evaluate the residual filling materials and the data statistically analyzed. Results: The least amount of residual filling materials was found in group D-ZOE (1.43) followed by group C-MTA-Fillapex (1.50) and B-Totalfill BC (1.57) respectively. While, the greater amount was in group A-Endosequence BC (1.87). Furthermore, the working length was re-gained 100% of all samples. Whereas, the patency regained in group A, B, C and D was 90%, 80%, 90%,100% respectively. Conclusion: None of the root canal filling materials could be completely removed. The greater amount of residual filling materials was observed in bioceramic sealers than the ZOE sealer. Furthermore, the working length regained 100% of samples. While, there was loss of patency in some cases